The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/1010824
|View full text |Cite
|
Sign up to set email alerts
|

Methane Source and Turnover in the Shallow Sediments to the West of Haima Cold Seeps on the Northwestern Slope of the South China Sea

Abstract: The Haima cold seeps are active cold seep areas that were recently discovered on the northwestern slope of the South China Sea (SCS). Three piston cores (CL30, CL44, and CL47) were collected within an area characterized by bottom simulating reflectors to the west of Haima cold seeps. Porewater profiles of the three cores exhibit typical kink-type feature, which is attributed to elevated methane flux (CL30) and bubble irrigation (CL44 and CL47). By simulating the porewater profiles of SO42-, CH4, PO43-, Ca2+, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 80 publications
(141 reference statements)
2
21
0
Order By: Relevance
“…Several sites with gas bubbling or shallow gas hydrates were also identified by hydroacoustic imaging and/or sediment coring around this area [24][25][26][27][28]. Recent studies have shown pronounced spatial and temporal changes in the intensity of methane seepage and the discharge of considerable amount of methane and DIC to the water column around the cold seeps [29][30][31]. In this study, we present seafloor observations and porewater geochemical data of six push cores, one piston core and three boreholes as well as fifteen bottom-water samples collected at two newly discovered seeps with weak activities and an intensely active seep in the Qiongdongnan Basin.…”
Section: Introductionmentioning
confidence: 99%
“…Several sites with gas bubbling or shallow gas hydrates were also identified by hydroacoustic imaging and/or sediment coring around this area [24][25][26][27][28]. Recent studies have shown pronounced spatial and temporal changes in the intensity of methane seepage and the discharge of considerable amount of methane and DIC to the water column around the cold seeps [29][30][31]. In this study, we present seafloor observations and porewater geochemical data of six push cores, one piston core and three boreholes as well as fifteen bottom-water samples collected at two newly discovered seeps with weak activities and an intensely active seep in the Qiongdongnan Basin.…”
Section: Introductionmentioning
confidence: 99%
“…Two headspace gas samples from the shallow sediment (~20 cmbsf) recovered at HM‐2 using pushcorer contained more than 99.5% methane with δ 13 C of −71.5‰ to 72.3‰, indicating a biogenic origin (Wei et al, ). It has been reported that gas originated from shallower than 2.3 km are exclusively biogenic (Fang et al, ; Feng et al, ); therefore, it is speculated that “HaiMa” cold seeps are fuelled by gas from strata shallower than 2.3 km. The seismic profile shows a Basal uplift deeply beneath “HaiMa” cold seeps (~3,000 ms and ~880 mbsf; Figure a) and large gas reservoirs characterized by low frequency (Figure b) on each side of the uplift (3,500 ms and ~1,280 mbsf).…”
Section: Resultsmentioning
confidence: 99%
“…The sources of inorganic carbon and types of redox reactions could be discriminated against by the δ 13 C DIC of pore water. In this work, the δ 13 C DIC values range from −22.67% (360 cm depth) to −26.12% (500 cm depth) in unit B (Table S2; Figure 2b), which are lower than the δ 13 C DIC values from the typical marine organic matters in the SCS (−20% ) [74,75]. Therefore, the lower δ 13 C DIC values indicate the occurrence of AOM [76], and in turn, lead to the precipitation of carbonates and decrease in the Ca 2+ and Mg 2+ concentrations (Table S2, Figure 2c,d).…”
Section: Aom Vs Omo Coupled With Fe/mn Reduction In Unit Bmentioning
confidence: 88%